MENINGKATKAN KUALITAS PENDIDIKAN MELALUI TEKNOLOGI INFORMASI - Husnul Fatarib (Ta'dib, 2011)
nformation technology (IT) has become major facilitators for business practices, has yielded great contribution towards fundamental changes upon organizational structures, operations, and management. Automatic Telling Machine (ATM) , e-commerce, online e-banking transfer, are the examples of the application of the technology and has made human’s life even easier. The advancement of IT also contributes to educational system. Web-based learnings (e-learnings) are continuously developed by IT practitioners. Profiles of educational institutions, starting from basic level up to university ones, are easily accessed by society regardless where they live due to IT developments. Therefore, there should be great attempts made the government, especially Ministry of Education and Culture, to ensure that IT can reach all level of society and get rid of the possibility of quality gaps of education.Kata kunci: kualitas pendidikan, teknologi, informasi